OPTN/SRTR 2011 Annual Data Report: Lung. (13th December 2012) - Valapour, M.; Paulson, K.; Smith, J. M.; Hertz, M. I.; Skeans, M. A.; Heubner, B. M.; Edwards, L. B.; Snyder, J. J.; Israni, A. K.; Kasiske, B. L.
Abstract : ABSTRACT Lungs are allocated in part based on the Lung Allocation Score (LAS), which considers risk of death without transplant and posttransplant. Wait‐list additions have been increasing steadily after an initial decline following LAS implementation. In 2011, the largest number of adult candidates were added to the waiting list in a single year since 1998; donation and transplant rates have been unable to keep pace with wait‐list additions. Candidates aged 65 years or older have been added faster than candidates in other age groups. After an initial decline following LAS implementation, wait‐list mortality increased to 15.7 per 100 wait‐list years in 2011. Short‐ and long‐term graft survival improved in 2011; 10‐year graft failure fell to an all‐time low. Since 1998, the number of new pediatric (aged 0–11 years) candidates added yearly to the waiting list has declined. In 2011, 19 pediatric lung transplants were performed, a transplant rate of 34.7 per 100 wait‐list years. The percentage of patients hospitalized before transplant has not changed. Both graft and patient survival have continued to improve over the past decade. Posttransplant complications for pediatric lung transplant recipients, similar to complications for adult recipients, include hypertension, renal dysfunction, diabetes, bronchiolitis obliterans syndrome, and malignancy.